2016
DOI: 10.1155/2016/7895234
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of River Water Downstream of a Large Tropical Hydroelectric Dam

Abstract: Water quality in the downstream river of a hydroelectric dam may be affected by the structural design and operation. To date, little is known about the water quality downstream of the largest dam in Malaysia, the Bakun hydroelectric dam. Therefore, the objective of the study was to determine the water quality downstream of the dam when the spillway was closed and when it was opened. Results of the study indicate that the dam plays a significant role in regulating the water quality downstream of it. When the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
6
23
0
Order By: Relevance
“…Both parameters were classified as Class I and/or Class II according to WQI. The low turbidity and TSS values in the present study were different from the high turbidity and TSS values observed in the downstream river of a new hydroelectric dam [30]. However, they are consistent with low turbidity (2-15 NTU) and TSS values (2-7 mg/L) recorded in the Batang Ai reservoir at 10 and 20 m depths [17], as suspended solids have settled at this 30-year-old reservoir [16].…”
Section: Physicochemical Parameters Of the Water Of The Downstream Risupporting
confidence: 60%
See 1 more Smart Citation
“…Both parameters were classified as Class I and/or Class II according to WQI. The low turbidity and TSS values in the present study were different from the high turbidity and TSS values observed in the downstream river of a new hydroelectric dam [30]. However, they are consistent with low turbidity (2-15 NTU) and TSS values (2-7 mg/L) recorded in the Batang Ai reservoir at 10 and 20 m depths [17], as suspended solids have settled at this 30-year-old reservoir [16].…”
Section: Physicochemical Parameters Of the Water Of The Downstream Risupporting
confidence: 60%
“…In Batang Ai Dam, the water intake for power operation is about 14 m below the surface, where the pH is predominantly acidic [15]. The increase in pH value at middle stream and downstream segments is attributable to dilution effect [30]. Water temperature ranged from 26.8 ± 0.7 ∘ C to 29.0 ± 1.4 ∘ C, where it decreased significantly ( ≤ 0.05) with distance from the dam.…”
Section: Physicochemical Parameters Of the Water Of The Downstream Rimentioning
confidence: 99%
“…Differences in structure and operation scheme of a dam may result in differences in water quality downstream. Recently, [22] demonstrated that the physicochemical characteristics of the river downstream of the Bakun Dam changed when the spillway was opened.…”
Section: Introductionmentioning
confidence: 99%
“…Physical structures such as dams and reservoirs were made to fulfil man's needs for the purposes of power generation, flood control, recreation, agriculture, and industry. Dam impoundment inevitably modifies the natural regime of its downstream rivers and has resulted in environmental degradation [1][2][3]. e fluctuations of flow and environmental conditions could lead to alteration of aquatic biodiversity in the downstream river [4].…”
Section: Introductionmentioning
confidence: 99%
“…e overall percentage of the fish family recorded in the study area 4. International Journal of Ecology hydroelectric dam[2].…”
mentioning
confidence: 99%